THE RELATIONSHIP BETWEEN SELF-ESTEEM AND SOCIAL SUPPORT WITH LIFE SATISFACTION OF JUNIOR HIGH SCHOOL STUDENTS: A LITERATURE REVIEW - Ayi Erdian; Herdi Herdi; Susi Fitri (LP2M IAI Al-Khairat Pamekasan, 2026)
This study aims to analyze the relationship between self-esteem and social support with the life satisfaction of junior high school students. It uses a literature review method as a way to address or highlight certain issues in providing reports that serve as the main data source for this study. The steps in the literature review include problem formulation, literature search, data evaluation, and analysis and interpretation. Relevant research sources include several national journals using the keywords: “life satisfaction adolescent,” “life satisfaction,” “self-esteem,” and “social support,” downloaded from Google Scholar, PubMed, and Sage Journals. The findings indicate that social support and self-esteem significantly influence life satisfaction, although the relationship between these variables is not always consistent across different contexts.